Ugotavljanje števila probiotičnih mikroorganizmov v krmnih mešanicah - Novak, Rok (Acta agriculturae Slovenica, 2008)
In animal nutrition a wide range of probiotic microorganisms belonging to lactic acid bacteria, yeasts and Bacillus genus are used. In this study we determined the number of microorganisms in different complete feed mixtures and premixtures, containing commercial probiotic supplements Bioplus 2b, Vebacor Biosaf. Bacillus subtilis and Bacillus licheniformis bacterial strains, which were isolated from product Bioplus 2b, were tested for antibiotic susceptibility, antimicrobial activity and ability to survive in simulated gastric and intestinal juice. We found that all tested products contained lower number of microorganisms than declared. The difference between declared and established value was the highest in products with Vebac and Biosaf. B. subtilis and B. licheniformis isolates were sensitive to all selected antibiotics except metronidazol. Survival test showed that simulated gastric or intestinal juices did not have considerable effect on spore survival, while vegetative cells of Bacillus strains were very sensitive to low pH and bile salts. B. licheniformis inhibited mostly Gram positive bacteria, while B. subtilis was more efficient against Gram negative bacteria.
Keywords: animal husbandry; živinoreja; prehrana živali; krmne mešanice; microbiology; mikrobiologija; probiotiki